Andrew Jackson Donelson papers - Donelson, Andrew Jackson, 1799-1871.; Burke, Pauline Wilcox; Donelson, Emily Tennessee, 1807-1836.; Martin, James Glasgow; Randolph, Meriwether Lewis, 1810-1837.; Wilcox, Mary Emily Donelson, 1829-1905.; United States. Constitution
Correspondence, journals, draft messages of Andrew Jackson, diplomatic papers, news clippings, scrapbook, sketches, photographs, and other papers pertaining to Donelson's service as Andrew Jackson's aide-de-camp (1820-1822) and presidential secretary (1829-1837), charge d'affaires to Texas (1844-1845), U.S. minister to Prussia (1846-1849), editor of the Washington Union (1851-1852), and vice-presidential candidate (1856). Subjects include the Nullification Crisis, 1828-1832; national economic policy; the move to recharter the Bank of the United States; French spoliation claims; matters involving George Poindexter; and the Eaton Affair (Petticoat Affair) involving John Henry Eaton and his wife, Peggy Eaton, and the subsequent cabinet reorganization of 1831. Subjects also include Andrew Jackson's presidential campaigns of 1824, 1828, and 1832; the annexation of Texas; plantation operations; and family affairs. Donelson family papers include those of Andrew Jackson Donelson's wife, Emily Tennessee Donelson; daughter, Mary Emily Donelson Wilcox; great-granddaughter, Pauline Wilcox Burke; James Glasgow Martin; and Meriwether Lewis Randolph. Correspondents include John Branch, William Gannaway Brownlow, James Buchanan, Benjamin F. Butler, R.K. Call, Lewis Cass, William J. Duane, John Henry Eaton, Andrew Jackson, Amos Kendall, Edward Livingston, Louis McLane, James Monroe, James K. Polk, Roger Brooke Taney, Zachary Taylor, John Tyler, Martin Van Buren, and Levi Woodbury.
Collection includes an original Dunlap & Claypoole printing of the United States Constitution with annotations by Edmund Pendleton as well as other documents concerning Virginia's ratification of the Constitution (1787-1788). Documents include Edmund Pendleton's address (1788 June 2) to the Virginia Convention, Journal of the Convention of Virginia (printed in June 1788 by Augustine Davis with notes in an unidentified hand), and memoranda of excerpts from the journal with notes by William Brent, Jr.
Microfilm edition available, in part
Microfilm produced from originals in the Manuscript Division.
Lawyer, editor, army officer, diplomat, and presidential secretary.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Branch, John, -- 1782-1863 -- Correspondence; Brent, William, -- 1783-1848.; Brownlow, William Gannaway, -- 1805-1877 -- Correspondence; Buchanan, James, -- 1791-1868 -- Correspondence; Butler, Benjamin F. -- 1795-1858 -- Correspondence; Call, R. K. -- 1791-1862 -- Correspondence; Cass, Lewis, -- 1782-1866 -- Correspondence; Duane, William J. -- 1780-1865 -- Correspondence; Eaton, John Henry, -- 1790-1856.; Eaton, John Henry, -- 1790-1856 -- Correspondence; Eaton, Peggy, -- 1799?-1879; Jackson, Andrew, -- 1767-1845.; Jackson, Andrew, -- 1767-1845 -- Correspondence; Kendall, Amos, -- 1789-1869 -- Correspondence; Livingston, Edward, -- 1764-1836 -- Correspondence; McLane, Louis, -- 1786-1857 -- Correspondence; Monroe, James, -- 1758-1831 -- Correspondence; Pendleton, Edmund, -- 1721-1803.; Poindexter, George, -- 1779-1853.; Polk, James K. -- 1795-1849 -- Correspondence; Taney, Roger Brooke, -- 1777-1864 -- Correspondence; Taylor, Zachary, -- 1784-1850 -- Correspondence; Tyler, John, -- 1790-1862 -- Correspondence; Van Buren, Martin, -- 1782-1862 -- Correspondence; Woodbury, Levi, -- 1789-1851 -- Correspondence; Donelson family; United States. -- Army -- Officers; Virginia. -- Convention -- (1788); Bank of the United States (1816-1836); Washington union; American newspapers -- Washington (D.C.); Cabinet officers -- United States; Constitutional history -- United States; Constitutions -- United States; Diplomatic and consular service, American -- Prussia (Germany); Elections -- United States -- 1824.; Elections -- United States -- 1828.; Elections -- United States -- 1832.; Elections -- United States -- 1856.; French spoliation claims; Nullification (States' rights); Plantations; Presidents -- United States -- Election; Germany -- Foreign relations -- United States; Prussia (Germany) -- Foreign relations -- United States; Texas -- History -- Republic, 1836-1846.; United States -- Economic conditions -- To 1865.; United States -- Economic policy -- To 1933.; United States -- Foreign relations -- Germany; United States -- Foreign relations -- Prussia (Germany); United States -- Politics and government -- 1783-1865.; United States -- Politics and government -- 1783-1789.; United States -- Politics and government -- 1829-1837.; Virginia -- Politics and government -- 1775-1865.; Army officers; Diplomats; Editors; Lawyers; Secretaries, Presidential